DNA sequencing of cytopathologically inconclusive EUS-FNA from solid pancreatic lesions suspicious for malignancy confirms EUS diagnosis - Plougmann, Julie Isabelle (Endosc Ultrasound, 2019)
BACKGROUND AND OBJECTIVES: EUS-FNA is inconclusive in up to 10%–15% of patients with solid pancreatic lesions (SPLs). We aimed to investigate whether supplementary genetic analyses with whole-exome sequencing add diagnostic value in patients with SPLs suspicious of malignancy but inconclusive EUS-FNA. PATIENTS AND METHODS: Thirty-nine patients, who underwent EUS-FNA of an SPL were retrospectively included. Three groups were defined: 16 (41.0%) had suspected malignancy on EUS confirmed by cytology (malignant), 13 (33.3%) had suspected malignancy on EUS but benign cytology (inconclusive), and 10 (25.6%) had benign EUS imaging and cytology (benign). Areas with the highest epithelial cell concentrations were macro-dissected from the FNA smears from each patient, and extracted DNA was used for whole-exome sequencing by next-generation sequencing of a selected gene panel including 19 genes commonly mutated in cancer. RESULTS: Pathogenic mutations in K-RAS, TP53, and PIK3CA differed significantly between the three groups (P < 0.001, P = 0.018, and P = 0.026, respectively). Pathogenic mutations in KRAS and TP53 were predominant in the inconclusive (54% and 31%, respectively) and malignant groups (81.3% and 50%, respectively) compared to the benign group (0%). Malignant and inconclusive diagnoses correlated strongly with poor overall survival (P < 0.001). CONCLUSION: Whole-exome sequencing of genes commonly mutated in pancreatic cancer may be an important adjunct in patients with SPLs suspicious for malignancy on EUS but with uncertain cytological diagnosis.